2017
DOI: 10.1111/echo.13563
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular obstruction caused by a large hiatal hernia

Abstract: A 76-year-old man was admitted to our emergency department owing to chest pain, which started immediately after lunch. Although electrocardiogram revealed ST-segment elevation with hyperacute T-wave changes in the anterior lead tracings, emergency coronary angiography revealed normal coronary arteries. Echocardiography revealed left ventricular (LV) compression with left ventricular obstruction (LVO) caused by an echogenic mass. Computed tomography clearly revealed compression of both left atrial (LA) and LV b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 2 publications
0
6
0
2
Order By: Relevance
“…CECT of the chest demonstrated that the stomach and part of the ascites had herniated into the thoracic cavity from the esophageal hiatus. It has been widely reported that gastrothorax can increase intrathoracic pressure and compress the heart and can even cause cardiac arrest ( 2 , 3 , 5 , 10 ). The increased BNP level on admission in this case might indicate diastolic dysfunction due to cardiac compression ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CECT of the chest demonstrated that the stomach and part of the ascites had herniated into the thoracic cavity from the esophageal hiatus. It has been widely reported that gastrothorax can increase intrathoracic pressure and compress the heart and can even cause cardiac arrest ( 2 , 3 , 5 , 10 ). The increased BNP level on admission in this case might indicate diastolic dysfunction due to cardiac compression ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hiatal hernia is not a rare complication, but it can be a serious complication of giant abdominal tumors caused by increased intra-abdominal pressure (1). A large hiatal hernia can increase intrathoracic pressure and compress the heart and even cause arrhythmia and cardiac arrest, which greatly increases the risks of anesthesia and the challenges of perioperative management (2)(3)(4)(5). We present a case in which a patient with a giant abdominal tumor and large hiatal hernia experienced a critical situation during anesthesia and surgery (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Chest pain was reported by 3 patients, but in 2 of the cases, the pain was retrosternal, described as distending and associated with food intake, and in the third case, it was pleural pain related to chest wall injury. Although most of the literature indicates a prevalence of gastrointestinal symptoms and specifically symptoms of gastroesophageal reflux disease and oesophagitis, some reports describe cases in which cardiologi-cal symptoms, such as haemodynamic instability caused by a large diaphragmatic hernia [31], changes suggesting an acute myocardial infarction [32], left ventricle compression by a large hernia [33] and fainting after a meal [34], dominate.…”
Section: Discussionmentioning
confidence: 99%
“…Hiatal hernia and changes in electrocardiogram. Changes in the electrocardiogram pattern and rhythm have been observed in patients with hiatal hernias [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. However, the linkage between these conditions has not been fully elucidated.…”
Section: Tension Gastrothorax As Hiatal Hernia Complicationmentioning
confidence: 99%
“…Hiatal hernia may be visualized in the transthoracic echocardiogram while it is encroaching on the posterior part of the left atrium and left atrioventricular junction [41]. Hiatal hernia is usually seen as an extracardiac posterior mass encroaching on the left atrial cavity, mimicking a left atrial mass on transthoracic echocardiography [25,[42][43][44][45][46][47][48][49][50][51][52][53][54]. However, this may not be obviously apparent since its visualization relates to the imaging plane and respiratory fluctuation [41].…”
Section: Tension Gastrothorax As Hiatal Hernia Complicationmentioning
confidence: 99%